The Effect of Diabetes Self-Management Education (DSME) on Blood Sugar Control in Patients with Diabetes Mellitus - Laili Nur Hidayati; Bekti Sukoco; Endah Purwanti (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus (DM) is a growing global health issue, both in terms of its prevalence and the impact of its complications. Controlling blood sugar levels is a key component in preventing DM complications. However, managing blood sugar remains challenging, primarily due to a lack of patient knowledge and skills in self-management. Diabetes Self-Management Education (DSME) is an educational approach designed to enhance patients' ability to independently manage their condition. This study aims to analyze the effect of DSME on blood sugar control in DM patients at Merauke Regional General Hospital. A pre-experimental design with a pretest-posttest approach without a control group was used. The sample consisted of 21 DM patients selected using probability sampling techniques. The intervention involved DSME delivered over four educational sessions, covering topics such as the concept of DM, dietary regulation, physical activity, and blood sugar monitoring. Blood sugar levels were measured before and after the intervention using a portable glucose meter. Data analysis was performed using repeated measures ANOVA. The average blood sugar levels of the patients decreased from 229 mg/dL before the intervention to 175 mg/dL at the first follow-up and 177 mg/dL at the second follow-up after the DSME intervention. The analysis showed a significant effect of DSME on reducing blood sugar levels (p < 0.05). DSME proved effective in improving blood sugar control in DM patients through structured education that supports self-care. This program also helps patients understand the importance of adopting a healthy lifestyle and adhering to therapy. Continuous implementation of DSME is recommended to improve the quality of care for DM patients and reduce the risk of long-term complications.